KEANEKARAGAMAN JENIS POHON DISEKITAR UNIVERSITAS SAN PEDRO, KOTA KUPANG NUSA TENGGARA TIMUR - Fahik, Mery (Jurnal Biogenerasi, 2024)
Biodiversity is one of the main components that determine the health and balance of an ecosystem. An important aspect of biodiversity is tree species diversity, which plays a crucial role in maintaining ecosystem functions and providing various ecosystem services. This research aims to identify the tree species diversity at San Pedro University to support academic activities and aid conservation efforts. The research employs a quantitative descriptive method with an exploratory survey. The study was conducted at 4 stations using the single plot method with purposive sampling. The identification results were analyzed descriptively using species diversity index, evenness index, dominance index, and species richness index. Tree species diversity comprises 13 families, encompassing 23 different tree species. Families with the highest number of individuals are Fabaceae, Arecaceae, and Euphorbiaceae. The tree diversity index at San Pedro University is 2.783, indicating that the tree species diversity on campus is in the moderate category. The tree dominance index is 0.076, indicating low tree species dominance. The tree evenness index is 0.888, close to one, indicating that the distribution of tree species on campus is quite even and stable. The tree species richness index is 4.330, indicating high tree species richness.